EVALUATION OF THE QUALITY OF ONLINE LEARNING USING THE ROUGH SET METHOD IN THE COVID 19 ERA - Ramdani Bayu Putra; Sarjon Defit; Hasmaynelis Fitri (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
The occurrence of the Covid 19 pandemic around the world has changed all human physical activities in all lines of life, including activities in carrying out the teaching and learning process in educational institutions. This study seeks to analyze and evaluate the quality of online learning in the Covid 19 era. Measuring the quality of online learning is carried out using the rough set method, where the aspects or attributes used to consist of learning motivation, cognitive and self-efficacy. This research was conducted on students of the Putra Indonesia University YPTK Padang during the Covid 19 pandemic. By using the rough set algorithm technique, it is expected that the pattern or combination between attributes can produce knowledge or information in predicting the quality of online learning in the Covid 19 era. The results of testing with the Rosetta application found that The combination of cognitive and self-efficacy is an attribute that directly determines the quality of online learning in the Covid 19 era